The Beijing Consensus and the New Silk Road in Africa: Chinese investments in new disputes of hegemony - Nascimento, Lucas Gualberto do (Conjuntura internacional, 2020)
This paper is going to analyze, from governmental and academic reports, the development of Sino-African relations mainly in the sphere of influence of the Forum on China-Africa Cooperation (FOCAC); and of the One Belt, One Road (OBOR) project, also known as the New Silk Road.